2023
DOI: 10.1126/science.abj8894
|View full text |Cite
|
Sign up to set email alerts
|

Past history of obesity triggers persistent epigenetic changes in innate immunity and exacerbates neuroinflammation

Abstract: Age-related macular degeneration is a prevalent neuroinflammatory condition and a major cause of blindness driven by genetic and environmental factors such as obesity. In diseases of aging, modifiable factors can be compounded over the life span. We report that diet-induced obesity earlier in life triggers persistent reprogramming of the innate immune system, lasting long after normalization of metabolic abnormalities. Stearic acid, acting through Toll-like receptor 4 (TLR4), is sufficient to remodel chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…However, the function of these newly found ATMs remains to be understood . Although this study suggests that weight loss promotes beneficial changes to ATMs, two recent papers demonstrate that weight loss induced by switching from high-to low-fat diet does not reverse the obesity-induced inflammatory phenotype of ATMs (Caslin et al, 2022;Hata et al, 2023). Both these studies show that formerly obese ATMs produce more inflammatory cytokines than lean ones, and in comparable amounts to obese ATMs upon stimulation with lipopolysaccharide (LPS).…”
Section: Efferocytosis and Phagocytosismentioning
confidence: 75%
“…However, the function of these newly found ATMs remains to be understood . Although this study suggests that weight loss promotes beneficial changes to ATMs, two recent papers demonstrate that weight loss induced by switching from high-to low-fat diet does not reverse the obesity-induced inflammatory phenotype of ATMs (Caslin et al, 2022;Hata et al, 2023). Both these studies show that formerly obese ATMs produce more inflammatory cytokines than lean ones, and in comparable amounts to obese ATMs upon stimulation with lipopolysaccharide (LPS).…”
Section: Efferocytosis and Phagocytosismentioning
confidence: 75%
“…The addition of other components such as hyperglycemia and low-HDL probably serve as precipitating and amplification factors over neuroinflammation. Several publications have begun to describe the relationship between systemic inflammation and neuronal loss [ 72 , 73 , 74 , 75 ]. Briefly, insulin resistance and hyperinsulinic states (such as obesity and hypertriglyceridemia) induce mitochondrial dysfunction in neurons, mitochondrial fission, and energy loss, suggesting that glycemic and lipidic dysmetabolism induce neuronal loss [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It indicated no matter developing into obesity status or from obesity to normal weight, as long as obesity had occurred in one's lifespan, blood pressure would be abnormal. Studies have found that this is caused by the hidden danger of immune cell abnormalities during the obesity period ( 24 ). We speculate that this might be due to a large amount of free fatty acids in the circulatory system of obese individuals, and these fatty acids can directly change the innate immune cells including monocytes and macrophages into inflammatory phenotypes, which are retained in the aging process of mice through “epigenetic memory” ( 25 ).…”
Section: Discussionmentioning
confidence: 99%